Understanding Sheng Nu ("Leftover Women"): the Phenomenon of Late Marriage among Chinese Professional Women. Issue 1 (25th January 2013) - To, Sandy
Abstract In the past few decades, there has been a rise in the number of single, unmarried Chinese professional women, which is known as the sheng nu or "leftover women" phenomenon. Through an interactionist grounded theory method, this study has located the interactional constraints faced by 50 single Chinese professional women that were issued by their male romantic partners and parents, respectively. "Discriminatory" and "controlling" gendered constraints issued by the women's male suitors and partners reflected the persistence of the Chinese patriarchal structure, and this was found to be the leading cause of the women being "leftover" in the marriage market. Parents' traditional views continued to exert strong influences on the women's marital choices, but this was seen to conflict with their more "modern" views toward advocating and supporting the women's strong economic achievements. The four different types of Chinese professional women that were constructed based on their different partner choice strategies not only gave rise to an in‐depth and nuanced understanding of the sheng nu phenomenon in China, but could also be generalized toward understanding the marital choices of single professional women in other patriarchal societies who faced similar dilemmas in reconciling interactional constraints imposed by men and parents alike.